2009
DOI: 10.1680/geng.2009.162.6.323
|View full text |Cite
|
Sign up to set email alerts
|

A review of field performance of stone columns in soft soils

Abstract: The behaviour of stone columns has yet to be captured fully by analytical and numerical techniques, and predicting column behaviour in soft cohesive soils brings specific challenges. This paper provides a comprehensive review and assessment of some aspects of field performance of stone columns in soft clays and silts, from both published and unpublished data and for loading over both wide areas (i.e. embankments) and small areas (i.e. footings). In particular, a new database of settlement improvement factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 29 publications
5
51
1
1
Order By: Relevance
“…Laboratory-based research, together with analytical modelling, numerical modelling and field observations, is well documented, and has contributed to improvements in efficiency and quality control (Hughes & Withers, 1974;Hughes et al, 1975;Aboshi et al, 1979;Balaam & Booker, 1981;Barksdale & Bachus, 1983;Charles & Watts, 1983;Alamgir et al, 1994;Hu, 1995;Balaam et al, 1977;Raju, 1997;Slocombe et al, 2000;Watts & Serridge, 2000;McKelvey, 2002;McKelvey et al, 2004;Pulko & Majes, 2005;Black, 2007;Black et al, 2007aBlack et al, , 2007bMcCabe et al, 2009). Stone columns are typically employed to support large raft foundations at relatively low or moderate loading conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory-based research, together with analytical modelling, numerical modelling and field observations, is well documented, and has contributed to improvements in efficiency and quality control (Hughes & Withers, 1974;Hughes et al, 1975;Aboshi et al, 1979;Balaam & Booker, 1981;Barksdale & Bachus, 1983;Charles & Watts, 1983;Alamgir et al, 1994;Hu, 1995;Balaam et al, 1977;Raju, 1997;Slocombe et al, 2000;Watts & Serridge, 2000;McKelvey, 2002;McKelvey et al, 2004;Pulko & Majes, 2005;Black, 2007;Black et al, 2007aBlack et al, , 2007bMcCabe et al, 2009). Stone columns are typically employed to support large raft foundations at relatively low or moderate loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach delivers good correlation with actual observed field behaviour for infinite groups, but discrepancies exist when it is applied to small-group column configurations. This is attributed to complex group interaction effects, which make confident predictions of settlement performance problematic (McCabe et al, 2009). The work reported in this paper addresses the limitations associated with previous investigations, and uses reduced scale physical models to provide valuable insight into the settlement performance of isolated and small groups of stone columns.…”
Section: Introductionmentioning
confidence: 99%
“…Yarı ampirik olan yöntem, taş kolon performansını etkileyen tüm parametreleri içermemesine rağmen, kullanımının basit olmasından dolayı en çok tercih edilen yöntemlerdendir [7]. Taş kolonların iyileştirme etkisi, başlangıç koşulları ile karşılaştırma yapılarak belirlenir.…”
Section: Priebe (1995)unclassified
“…Ambily and Gandhi [2] developed a design charts to estimate the settlement of the stone column reinforced ground through the model tests and finite element based numerical analyses using unit cell concept. McCabe et al [25] compared the measured and predicted settlement improvement factors of the stone column improved grounds subjected to embankment and footing loading from 20 recorded case histories on soft cohesive soil. A comparison was also made based on the predicted and measured settlement improvement factors among different construction techniques of the stone columns and concluded that the dry bottom feed techniques is preferred method for the stone column construction in soft cohesive soil.…”
mentioning
confidence: 99%